Implementasi Kebijakan Ketahanan Pangan di Kabupaten Tasikmalaya - Ade Iskandar (e-JKPP, 2015)
Indonesia as agricultural country ought to provide the food for the resident of its but still conduct the food import. Though elementary requirement food which must be fulfilled by each;every citizen. So that, need the alternative to support the food resilience that is Implementation of Policy of Food Resilience in Regency Tasikmalaya. But in its implementation is his rentan continueing. This research wish to know the role and sinergitas stakeholders, factors of supporter or its implementation continueing resistor, and also benefit of implementation of Policy of Food Resilience in Regency Tasikmalaya, in supporting food resilience. its Research type is descriptive with the approach qualitative and analyse its data, analysis opened by Bogdan, Taylor cover the phase pralapangan, field and pasca field.Result of research show the role and sinergitas stakeholders in continueing of implementation of Implementation of Policy of Food Resilience in Regency Tasikmalaya, not yet optimal. Its supplementary factor because fertile land;ground, wide lawn potency enough, medium and prasarana and also available institute represent the governmental program. its Resistor factor because technical problems is which not yet been finished and decrease it motivate the policy perpetrator. Implementation of Policy of Food Resilience in Regency Tasikmalaya, useful support the food resilience in the Regency minimize mounted by domestic.